2007
DOI: 10.1091/mbc.e07-02-0188
|View full text |Cite
|
Sign up to set email alerts
|

A Knockout Mouse Approach Reveals that TCTP Functions as an Essential Factor for Cell Proliferation and Survival in a Tissue- or Cell Type–specific Manner

Abstract: Translationally controlled Tumor Protein (TCTP) is an evolutionally highly conserved protein which has been implicated in many cellular functions that are related to cell growth, death, and even the allergic response of the host. To address the physiological roles of TCTP, we generated TCTP knockout mice by targeted gene disruption. Heterozygous mutants appeared to be developmentally normal. However, homozygous mutants (TCTP ؊/؊ ) were embryonic lethal. TCTP ؊/؊ embryos were smaller in size than the control li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 29 publications
11
150
0
Order By: Relevance
“…Finally, recombinant TCTP increases ERK 1/2 activation and inhibits VSMC apoptosis. TCTP is an evolutionarily conserved protein of crucial Caspase-3 activation fosters nanovesicle release I Sirois et al importance during development 25 and for intracellular apoptosis inhibition. 26,27 The present work demonstrates that TCTP also displays significant extracellular antiapoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recombinant TCTP increases ERK 1/2 activation and inhibits VSMC apoptosis. TCTP is an evolutionarily conserved protein of crucial Caspase-3 activation fosters nanovesicle release I Sirois et al importance during development 25 and for intracellular apoptosis inhibition. 26,27 The present work demonstrates that TCTP also displays significant extracellular antiapoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the anti-apoptotic activity of TCTP has been reported on numerous occasions and in a range of different settings, which will be discussed below. Major support for the cytoprotective role of TCTP came from gene-knockout studies in mice, which demonstrated that TCTP-knockout was embryonic lethal, due to excessive apoptosis at an early embryonic state (Susini et al 2008;Chen et al 2007a;Koide et al 2009). The following mechanisms have been proposed to underlie the anti-apoptotic activity of TCTP/fortilin: …”
Section: Anti-apoptotic Activity: Discovery and Mechanismsmentioning
confidence: 99%
“…The most impressive evidence for the importance of TCTP in early development was provided by TPT1-gene-knockouts in mice, which resulted in embryonic lethality (Susini et al 2008;Chen et al 2007a;Koide et al 2009). The explanation typically given for this effect was 'excessive apoptosis at an early embryonic state' (Susini et al 2008;Chen et al 2007a), whereas another report reasons that the lack of TCTP results in an overactivity of the BMP4 (bone morphogenetic protein 4) pathway, which is normally inhibited by TCTP (Koide et al 2009). The authors of this paper also show that in Xenopus embryos TCTP/fortilin is particularly important for the formation of neural tissue, even in the brain.…”
Section: Roles For Tctp In Early Developmentmentioning
confidence: 99%
“…This observation is consistent with the demonstration that TCTP overexpression in mice results in systemic hypertension (Kim et al, 2008b); (2) TCTP interacts with protein synthesis elongation factor eEF1A and negatively regulates the guanosine-nucleotide-exchange reaction on eEF1A (Cans et al, 2003); (3) a study using gene knockdown in Drosophila reported the activity of TCTP as a guanine-nucleotide-exchange factor for the small GTPase, Rheb, and indicated involvement of TCTP in the target of rapamycin (TOR) signalling pathway (Hsu et al, 2007); however, recent results from our own (Wang et al, 2008) and two other laboratories (Chen et al, 2007;Rehmann et al, 2008) are not compatible with this conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Gene-knockout studies have established the importance of TCTP in developmental regulation. Homozygous, TCTP-null mice (Chen et al, 2007;Susini et al, 2008) and dTCTP-null mutants in Drosophila (Hsu et al, 2007) exhibit embryonic lethality. Gene knockdown in Arabidopsis generated a male gametophytic phenotype and developmental alterations (Berkowitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%